Sustainable Workforce in a Green Era: Indonesia’s Energy Sector Transition - Simbolon, Sahat; Simbolon, Dwi Maria (International Journal of Energy Economics and Policy, 2024)
The purpose of this study is to determine and analyze the effect of renewable energy transition variables and economic viability in the Indonesian employment industry on the balance of business sustainability through social and environmental development as an intervening variable. The subjects of this study are small, medium, and large industry owners in Indonesia, totaling 5,993,566 business units. The variables in this study are independent variables, namely the variables of renewable energy transition and economic viability in the Indonesian labor industry, while the dependent variable is the balance of business sustainability, and the intervening variable is the variable of social and environmental considerations. The results of the data analysis are made through SEM analysis through SMART PLS 4.0 software. From the results of existing research, it is concluded that partially renewable energy transition variables and viability variables in the Indonesian labor industry have a direct effect on the balance of business sustainability and social and environmental consideration variables. Simultaneously, the renewable energy transition variable and the viability variable in the Indonesian labor industry indirectly affect the business sustainability balance variable through social and environmental considerations as intervening variables. With the renewable energy transition process, it will have an impact on people’s good social lives because there is no threat of environmental damage or natural disasters, so the environment is safe, the industry creates a technology transfer process, and it increases economic viability in the labor industry in Indonesia in order to create quality human resources. With this transition process, trained human resources are needed and are also able to adapt well to the transition process and technology transfer in order to balance the sustainability of industrial businesses.